Welcome to Scribd, the world's digital library. Read, publish, and share books and documents. See more
Download
Standard view
Full view
of .
Look up keyword
Like this
1Activity
0 of .
Results for:
No results containing your search query
P. 1
Yang X - Approximations for Constant e and Their Applications - J. Math. Anal. & Appl. 262 (2001) 651-659

Yang X - Approximations for Constant e and Their Applications - J. Math. Anal. & Appl. 262 (2001) 651-659

Ratings: (0)|Views: 10|Likes:
Published by Renee Bravo

More info:

Published by: Renee Bravo on Aug 01, 2010
Copyright:Attribution Non-commercial

Availability:

Read on Scribd mobile: iPhone, iPad and Android.
download as PDF, TXT or read online from Scribd
See more
See less

07/31/2010

pdf

text

original

 
Journal of Mathematical Analysis and Applications
262,
651–659 (2001)doi:10.1006/jmaa.2001.7592, available online at http://www.idealibrary.com on
 Approximations for Constant
e
and Their Applications
Xiaojing Yang
 Department of Mathematics, Tsinghua University, Beijing, People’s Republic of ChinaSubmitted by L. Debnath
Received January 9, 2001Two equalities for the approximation of constant
e
and their applications areconsidered.
2001 Academic Press
 Key Words:
Hardy’s inequality; Carleman’s inequality.
1. INTRODUCTIONIt is well known that the constant
e
plays an important role in many areasof mathematics. It is involved in many inequalities, identities, series expan-sions, and some special functions. The well known Hardy’s inequality andCarleman’s inequality are good examples of applications of approximationof 
e
.Recently, there have been many results in generalizing the above men-tioned two inequalities by using better approximations of 
e
. In [1], Yangand Debnath obtained the inequalities
e
1
12
n
+
56
<
1
+
1
n
n
< e
1
12
n
+
1
(1.1) As an application of (1.1), they proved the following strengthenedCarleman’s inequality
n
=
1
a
1
a
2
···
a
n
1
n
< e
n
=
1
1
12
n
+
1
a
n
(1.2) where
a
n
0,
n
=
1
2

, and 0
<
n
=
1
a
n
<
.In [2], Yang showed that for
x >
0,
e
1
12
x
+
1
<
1
+
1
x
x
< e
1
12
x
+
1
(1.3)
6510022-247X/01 $35.00
Copyright
2001 by Academic Press All rights of reproduction in any form reserved.
 
652 xiaojing yang
 As an application of (1.3), he obtained the following strengthenedHardy’s inequality
n
=
1
λ
n
+
1
a
λ
1
1
a
λ
2
2
···
a
λ
n
n
1
/σ 
n
< e
n
=
1
1
λ
n
2
σ 
n
+
λ
n
λ
n
a
n
(1.4) where 0
< λ
n
+
1
λ
n
,
σ 
n
=
nm
=
1
λ
m
,
a
n
0, 0
<
n
=
1
λ
n
a
n
<
.Sandor and Debnath [3] showed that
e
 
x
1
+
x<
1
+
1
x
x
< e
2
x
+
12
x
+
1
(1.5)holds for all
x >
0.In [4], Xie and Zhong improved (1.3) and obtained the inequalities
e
1
714
x
+
12
<
1
+
1
x
x
< e
1
612
x
+
11
for
x >
0
(1.6) As an application of (1.6), they replaced the right side of (1.4) by asharper one:
e
n
=
1
1
6
λ
n
/
12
σ 
n
+
11
λ
n

λ
n
a
n
.The author of this paper [5] obtained a better approximation of 
e
than(1.3),
1
+
1
x
x
< e
1
6
k
=
1
b
k
1
+
x
k
(1.7) where
x >
0,
b
1
=
12
,
b
2
=
124
,
b
3
=
148
,
b
4
=
735760
,
b
5
=
111280
,
b
6
=
1945580608
.It is conjectured in [5] that if the following equality holds
1
+
1
x
x
=
e
1
k
=
1
b
k
1
+
x
k
x >
0
(1.8)then
b
k
>
0,
k
=
1
2

. As an application of (1.7), Yang [5] obtained the following strengthenedCarleman’s inequality
n
=
1
a
1
a
2
···
a
n
1
n
e
n
=
1
1
12
n
+
1
124
n
+
1
2
148
n
+
1
3
a
n
(1.9) where
a
n
0, 0
<
n
=
1
a
n
<
.In this paper, two equalities are given, which improve the inequalities(1.3) and (1.7); the conjecture in [5] is also proved. As applications, Hardy’sinequality and Carleman’s inequality are strengthened.
 
 approximations for constant
e
653
2. MAIN RESULTS
Theorem 1.
For 
x >
0
, let
1
+
xx
x
=
e
1
k
=
1
b
k
1
+
x
k
(2.1)Then
b
k
>
0
,
k
=
1
2

, and
b
k
nk
=
1
satisfy the following recursion formula:
b
1
=
12
b
n
+
1
=
1
n
+
1
1
n
+
2
n
=
1
b
n
+
2
n
=
1
2

(2.2)
Theorem 2.
For 
x >
0
, let
1
+
xx
x
=
e
1
k
=
1
a
k
2
x
+
1
k
(2.3)
Then the
a
k
nk
=
1
satisfy the following recursion formula
a
1
=
1
a
n
+
1
=
c
n
+
1
+
n
=
1
n
+
1
n
+
1
a
c
n
+
1
n
=
1
2

(2.4) where
c
m
=
1
m
if 
m
is odd,
1
m
+
1
if 
m
is even.Moreover, for
n
=
1
2

,
a
2
n
=
a
2
n
+
1
<
0
 Proof of Theorem
1. Let
=
11
+
x
. Then 0
< y <
1 and (2.1) is written as
k
=
1
b
k
k
=
1
11
1
e
(2.5)Denote
h
=
11
1
/y 
/e
. Then ln
h
=
1
+
1
ln
1
=
1
+ 
1
n
=
1
n
1
/n
=
n
=
1
n
/n
n
+
1

, hence
h
=
e
n
=
1
nn
n
+
1

You're Reading a Free Preview

Download
scribd
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->